IMPLEMENTASI PROGRAM PEMBERIAN MAKANAN TAMBAHAN BAGI ANAK YANG BERESIKO STUNTING - Dwi Mayla, Jesika; Isabella, Isabella; Adi Putra, Dwiki (Governance, 2025)
This research examines the implementation of a supplementary feeding program (PMT) for children at risk of stunting in Seberang Ulu 1 District, using Edward III's Implementation Theory, which addresses communication, resources, disposition, and bureaucratic structure. A qualitative case study approach was used, involving detailed interviews with health workers, posyandu cadres, and parents, alongside field observations and document analysis. The study finds that human resources, such as health instructors and posyandu cadres, are effectively utilized, and community engagement is high with mostly positive feedback. However, there is a small group of individuals who do not fully grasp the program’s benefits, highlighting a need for better public education. Overall, the program is operating effectively, though it faces challenges including limited budget, insufficient equipment, and some bureaucratic inefficiencies. To enhance the program’s impact, recommendations include improving resource allocation, streamlining bureaucratic processes, and increasing public education efforts to ensure a broader understanding and participation.